Complete mitochondrial genome of Canis lupus campestris. (27th August 2013) - Zhang, Honghai; Zhang, Jin; Zhao, Chao; Chen, Lei; Sha, Weilai; Liu, Guangshuai
Abstract: In this study, blood sample was obtained from a female Mongolian wolf ( Canis lupus campestris ) captured from Mongolia and its complete mitochondrial genome was sequenced for the first time.